Collision Diagram Analysis and Weighted Ranking of Accident-Prone Areas (Black Spots) on the Road Network of Padangsidimpuan City - Ahmad Rafii (PT Inovasi Pratama Internasional, 2026)
Padangsidimpuan City records traffic accidents concentrated on several road segments, yet mitigation efforts have generally focused on identifying accident-prone locations without examining collision characteristics. This study aims to rank accident-prone areas (black spots) using a multi-criteria weighting method, analyze collision patterns through collision diagrams, identify dominant contributing factors, examine the relationship between road geometry, vehicle speed, and accident patterns, and formulate segment-specific countermeasures. A quantitative descriptive approach was employed using 2021 traffic accident records from the Padangsidimpuan Traffic Police together with field surveys of road geometry and spot speeds. Black-spot ranking was based on casualty severity, road function, road status, and material losses. The results identified Jenderal Sudirman Road as the highest-ranked black spot (score = 49), followed by H.T. Rizal Nurdin Road (47), Abdul Haris Nasution 1 Road (35), Raja Inal Siregar Road (31), and Imam Bonjol Road (30). Collision diagram analysis identified head-on collisions as the dominant crash pattern, with Jenderal Sudirman Road recording the highest proportion (5 of 9 crashes; 55.6%). Human factors, particularly excessive speed and driver negligence, were the dominant contributing factors, reinforced by inadequate road infrastructure, including the absence of speed-limit signs, black-spot warning signs, and median separation. The study recommends speed management measures, installation of warning signs and rumble strips, median or centerline improvements, and implementation of a School Safety Zone (ZoSS) on school-front road segments. These findings provide practical guidance for transportation agencies and road authorities in prioritizing data-driven road safety improvements.